Systems and methods that facilitate data mining - TANG ZHAOHUI; CRIVAT IOAN B; GORBACH IRINA G; IYER RAMAN S; MACLENNAN C. J; KIM PYUNGCHUL (2006)
A system that facilitates data mining comprises a reception component that receives command(s) in a declarative language that relate to utilizing an output of a first data mining model as an input to a second data mining model. An implementation component analyzes the received command(s) and implements the command(s) with respect to the first and second data mining models. In another aspect of the subject invention, the reception component can receive further command(s) in a declarative language with respect to causing one or more of the first and second data mining models to output a prediction, the prediction desirably generated without prediction input, the implementation component causes the one or more of the first and second data mining models to output the prediction.